PENERBITAN CEK SEBAGAI ALAT PEMBAYARAN DAN PERMASALAHANNYA PADA LEMBAGA PERBANKAN - M. Zen Abdullah (Jurnal Ilmiah Universitas Batanghari Jambi, 2008)
As a financial institution that has a strategic role in the national economic growth, a bank should be managed professionally, rationally and accountably in addition to having strong commitment to protect its customers from any wrong doing. In order that banking system is sound, dynamic, profesional and accountable,banks should operate under several principles such as prudentiality, safety, profitability and efficiency.